2009
DOI: 10.1080/10717540802517951
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of novel pro-apoptotic agent DM-PIT-1 in PEG-PE-based micelles alone and in combination with TRAIL

Abstract: PURPOSE Develop and characterize a micellar formulations of N-{[(2-hydroxy-5-nitrophenyl)amino]carbonothioyl}-3,5-dimethylbenzamide (DM-PIT-1) – a new small molecule non-lipid antagonist of phopshotidylinositol-3.4.5-triphopshate and inhibitor of the PI3-kinase pathway. METHODS Micelle-forming PEG2000-PE was used to solubilize DM-PIT-1. To improve the specificity of the micellar DM-PIT-1, cancer-targeting anti-nucleosomal mAb2C5 antibodies as well as Tumor necrosis factor-Related Apoptosis-Inducing Ligand (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…A2780 is resistant to TRAIL-induced toxicity and as such, TRAIL micelles have no cytotoxic activity alone. Consistent with our previous data showing synergy of DM-PIT-1 with TRAIL in TRAIL-resistant cell lines (Skidan et al, 2009;Miao et al, 2010), the addition of TRAIL to the NCL-176 and NCL-240 formulations resulted in a markedly increased cytotoxicity of formulations ( Figure 4B). …”
Section: Drug-loaded/trail-modified Combination Micellessupporting
confidence: 79%
See 3 more Smart Citations
“…A2780 is resistant to TRAIL-induced toxicity and as such, TRAIL micelles have no cytotoxic activity alone. Consistent with our previous data showing synergy of DM-PIT-1 with TRAIL in TRAIL-resistant cell lines (Skidan et al, 2009;Miao et al, 2010), the addition of TRAIL to the NCL-176 and NCL-240 formulations resulted in a markedly increased cytotoxicity of formulations ( Figure 4B). …”
Section: Drug-loaded/trail-modified Combination Micellessupporting
confidence: 79%
“…TRAIL micelles were prepared by the thin-film hydration method as described previously (Skidan et al, 2009). Briefly, PEG 2000 -DSPE dissolved in chloroform was added to roundbottomed flasks.…”
Section: Formulation and Characterization Of Trail-modified Micellesmentioning
confidence: 99%
See 2 more Smart Citations
“…This targeted delivery system resulted in a higher accumulation of the drug in tumors and stronger antitumor and anti-angiogenic effects in U87MG and PC3 tumors in nude mice compared with control treatment with a sham-targeted drug [71]. The PI3-kinase pathway has also been targeted using tumorcell-specific micelles [72]. This study showed that inclusion of the poorly soluble PI3-kinase pathway inhibitor DM-PIT-1 into micelles improved its solubility.…”
Section: Malignant Diseasesmentioning
confidence: 90%